THE HIGH-TEMPERATURE (OXIDATION-RESISTANT) FIBROVER-MIKULITOBETON COMPOSITES WITH THE PUMICE APPLICATION - A. Z. Zhukov; G. N. Khadzhishalapov; T. A. Khezhev; Kh. A. Khezhev (Вестник Дагестанского государственного технического университета: Технические науки)
High-temperature (oxidation-resistant) composites with the application of portland cement, distended vermiculite, pumice, basaltic fibers are developed. Are investigated compositions and properties of the vermikulitobeton composites. Are obtained the mathematical models of the dependence of the strength of the high-temperature (oxidation-resistant) fibrovermikulitobeton composites on the percentage of reinforcement and ratio of fiber length to their diameter.